1997
DOI: 10.1182/blood.v90.8.3187
|View full text |Cite
|
Sign up to set email alerts
|

Increased Phagocyte FcγRI Expression and Improved Fcγ-Receptor–Mediated Phagocytosis After In Vivo Recombinant Human Interferon-γ Treatment of Normal Human Subjects

Abstract: Recombinant human interferon-γ (rhIFN-γ) decreases the frequency of serious infections in patients with chronic granulomatous disease (CGD) through an unknown mechanism. To test the hypothesis that it exerts a beneficial effect by enhancing clearance of microbes from the bloodstream and tissues, normal human subjects were treated in vivo with rhIFN-γ. Phagocyte opsonic receptor expression, serum opsonin levels, and phagocytosis of bacteria were then measured. A 4.7-fold increase in neutrophil expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 41 publications
2
52
2
3
Order By: Relevance
“…The percentage of neutrophils expressing FcgRI increased after IFN-g administration, whereas no effect was measured on the MFI of FcgRI on neutrophils. The latter finding is in contrast to the study by Schiff et al [43], who administered IFN-g (50 mg m 22 day 21 ) to healthy subjects for 2 days, and noticed an increased MFI of FCgRI expression on neutrophils. We have no clear explanation for these different results, except that Schiff injected less IFN-g.…”
Section: Discussioncontrasting
confidence: 99%
“…The percentage of neutrophils expressing FcgRI increased after IFN-g administration, whereas no effect was measured on the MFI of FcgRI on neutrophils. The latter finding is in contrast to the study by Schiff et al [43], who administered IFN-g (50 mg m 22 day 21 ) to healthy subjects for 2 days, and noticed an increased MFI of FCgRI expression on neutrophils. We have no clear explanation for these different results, except that Schiff injected less IFN-g.…”
Section: Discussioncontrasting
confidence: 99%
“…These ®ndings are consistent with previous studies demonstrating the pathological roles of both humoral and cell-mediated immunity in DM (9). Furthermore, IFN-g is a potential activator of macrophage and enhances the expression of FcgR (10). It is therefore possible that the production of PA-IgG, activation of macrophage and subsequent FcgR-mediated hemophagocytosis occurred as a result of underlying DM.…”
Section: Discussionsupporting
confidence: 92%
“…62 Furthermore, FccRI is highly competent in phagocytosis, 63 and important in the uptake of bactaeremia-causing bacteria such as Staphylococcus aureus by human neutrophils. 64 However, FccRIIA-transfected non-phagocytic cells are able to phagocytose Escherichia coli efficiently 65 and we found that IgG2-mediated bacterial uptake has a greater dependency on FccRIIA over FccRI. Hence, both FccRI and FccRIIA are important in mediating phagocytosis in THP-1 cells, and the relative importance of each FccR differs, depending on the antibody subclass in question.…”
Section: Discussionmentioning
confidence: 67%